A Descriptive and Geospatial Analysis of Environmental Factors Attributing to Sudden Unexpected Infant Death. (June 2019) - Drake, Stacy A.; Wolf, Dwayne A.; Yang, Yijiong; Harper, Sherhonda; Ross, Jennifer; Reynolds, Thomas; Giardino, Eileen R.
Abstract : Abstract: This study examined medicolegal death investigation records and autopsy reports of a medical examiner's office to identify the circumstances surrounding sudden unexpected infant deaths (SUID) and geospatial analyses to pinpoint areas of infant death concentration. Analysis of 732 records of SUID deaths occurring in a 10-year span resulted in the conclusion that environmental factors associated with the sudden death were to some extent modifiable. Co-sleeping (sharing a sleeping surface, or bed-sharing) on various surfaces (mattress, pallet, couch) occurred in 53.4% of the infant deaths. Geographic areas where the largest number of deaths occurred were characterized as areas of high poverty level. The inclusion of additional information at the time of investigation (eg, alcohol and tobacco use of co-sleepers, illness of others in household, exceptions to normal sleep routine of infant) may aid in identifying modifiable circumstances to reduce infant mortality attributable to sudden infant death.